Digital skills and self-efficacy: Unpacking their influence on faculty research engagement - Disastra, Ganjar Mohamad; Noermijati, Noermijati; Irawanto, Dodi Wirawan; Moko, Wahdiyat (Edelweiss Applied Science and Technology, 2024)
Drawing from social cognitive theory, this study investigates the mediating role of self-efficacy in the relationship between Digital Skills and Research Engagement among faculty in Higher Education. Using a cross-sectional research design, data were collected from 211 faculty members at a Private University in Indonesia. The Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was applied to test the hypotheses proposed in research model. The results indicate that only three dimensions of Digital Skills - Information and Data Literacy, Communication and Collaboration, and Problem-Solving - have a positive and significant effects on Research Engagement. On the other hand, Content Development and Safety show insignificant effects. Additionally, Self-Efficacy have a positive and significant direct effect on Research Engagement and acts as a mediator between Information and Data Literacy, Problem-Solving, and Research Engagement. These results underscore the importance of developing targeted professional development programs that enhance digital skills and self-efficacy, ultimately contributing to improved research productivity and academic success. The study highlights the need for institutions to invest in faculty training and support systems that promote digital literacy and self-efficacy, fostering a more engaged and effective academic workforce.